2021
DOI: 10.1134/s102833582101002x
|View full text |Cite
|
Sign up to set email alerts
|

The Delay in Cavity Formation in the Intrusive Mode of Coalescence of a Freely Falling Drop with a Target Liquid

Abstract: The dynamics of a cavity formed in the intrusive mode of coalescence of a freely falling drop flowing smoothly into a liquid have been traced for the first time by the methods of photo and video registration. The cavity begins to form when the bottom part of the drop submerges, when the fluid coalescence line contracts to the center of the flow, and, simultaneously with the annihilation of the drop surface, the surface of the target liquid is restored. In this case, the orientation of ligaments (thin trickles)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The experiments carried out showed that the observed patterns of the drop substance transfer in the target fluid are naturally divided into two groups. Drops approaching the surface at a low velocity at which the APSE exceeds the KE E σ > E k , smoothly flow in and form a compact colored volume in the thickness of the target fluid [77]. The surface of a fluid with a partially infused drop remains convex for some time.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The experiments carried out showed that the observed patterns of the drop substance transfer in the target fluid are naturally divided into two groups. Drops approaching the surface at a low velocity at which the APSE exceeds the KE E σ > E k , smoothly flow in and form a compact colored volume in the thickness of the target fluid [77]. The surface of a fluid with a partially infused drop remains convex for some time.…”
Section: Resultsmentioning
confidence: 99%
“…13 ms. The vortex ring itself begins to form and descend after the end of a series of fast processes [77].…”
Section: Introductionmentioning
confidence: 99%
“…At a low contact velocity of the drop, the shape and internal structure of the area of colored liquid in the cuvette resembles a "mushroom-shaped" dusty cloud of a groundbased nuclear explosion [23][24][25]. In this range of parameters, the drop inflows directly into the liquid, and the cavity is formed with a delay of about 10 ms [26].…”
Section: Introductionmentioning
confidence: 99%